Standardization and Risk Governance A Multi-Disciplinary Approach - Olsen, Odd Einar (Taylor & Francis, 2019)
This multi-disciplinary book conceptualizes, maps, and analyses ongoing standardization processes of risk issues across various sectors, processes, and practices. Standards are not only technical specifications and guidelines to support efficient risk governance, but also contain social, political, economic, and organizational aspects. This book presents a variety of standardization processes and applications of standards that may influence our judgements of risk, the organizing of risk governance, and, accordingly, our behaviour. Standardization and standards can impact risk governance in different ways. The most important lessons drawn from the present volume can be summarized in three areas: (1) how standardization might impact on power relations and interests; (2) how standardization may change flexibility in decision-making, communication, and cooperation; and (3) how standardization could (re)direct attention and risk perception. The volume's aim is to present an analysis of standardization processes and how it affects our thinking about risk, how we organize risk governance, and how standardization may influence risk management. In so doing, it contributes to a more informed discourse regarding the use of standards and standardization in contemporary risk management. Standardization and Risk Governance will be of great interest to students of risk, standardization, global governance, and critical security studies.